PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PT ANGKASA PURA (Persero) HUSEIN SASTRANEGARA BANDUNG - Rd. Allya Surya Purnamasari , Romat Saragih (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2018)
Basically, every organization need a human resource that play an active role in it which will determine the success of the organization. To manage the human resource, a leader figure is needed to be able developing and achieving oganization's target which has been defined before. Organization's goal can be achieved depending on how employee's performance which has been generated in it as well as PT Angkasa pura II Husein Sastranegara Bandung. On the obtained data, there is a significant inrease in employee's delay, where an employee's presence can affect work productivity ehich can impact on employee's performance. This study is intend to determine the influence of Transformational Leadership Style as an Independent Variable on Employee's Performance asn Dependent Variable on PT Angkasa Pura II Husein Sastranegara Bandung.This research is a quantitative research model. The research method is using a descriptive-causel method. Using a simple random sampling type. Collecting data was done by distributing questionnaries to 75 employees of PT Angkasa Pura II Husein Sastranegara Bandung. The data analysis technique has been used is simple linear regression analysis. Based on research result, can be concluded that transformasional leadership style of PT Angkasa Pura II Husein Sastranegara Bandung is in a good category and the employee's performance of PT Angkasa Pura II Husein Sastranegara Bandung is in good category too. Based on the result of coefficient determination test that the Transformational Leadership Style is affect the employee's performance in the amount of 43.3% and the other 56,7% is influence other variables. Also on T test shows that Transformational Leadership has a significant influence on employee's performance. Key Words: Human Resource Management, Leadership, Leadership Style, Transformational Leadership, Employee's performance